Challenges facing school governing bodies in managing discipline among youth at selected rural secondary schools in Shiluvane Circuit in Limpopo Province - Seoka, Malope Frank (My University, 2019)
The purpose of this study was to explore the challenges facing School Governing Bodies in managing discipline among youth at selected rural secondary schools in Shiluvane Circuit in Limpopo Province. The researcher employed an interpretative qualitative research approach using case study design. The study focused on two rural secondary schools which were purposefully sampled. The research concentrated only on the views of the principals, educators, learners and parents who are members of School Governing Bodies regarding the challenges facing school governing bodies in managing discipline among youth at selected rural secondary schools in Shiluvane Circuit in Limpopo Province. The target sample for this study consists of five educators, five learners who are the chairperson, deputy chairperson, secretary, deputy secretary and the treasurer who are members of Representative Council of Learners, one principal and five parents, who are members of School Governing Body at each selected rural secondary school. The total number of participants is thirty-two. Data were collected through document review, semi-structured interviews and observation. Data were analysed inductively which implied that data were transcribed, coded and categorised into themes. The findings revealed that the target School Governing Bodies still find themselves in a predicament in applying contemporary disciplinary measures after corporal punishment was abolished. Participants identified some of the challenges they face such as bullying and intimidation, sexual harassment, drugs and alcohol abuse and carrying of dangerous weapons to schools. Participants indicated that alternative measures to corporal punishment were not very effective in curbing learner indiscipline in schools and found it difficult to choose and implement the correct alternatives to corporal punishment. The study recommended that School Governing Bodies should orientate learners about the Code of Conduct and school rules, and the consequences of breaking them could lead to disciplinary action, detention, suspension and expulsion. Parents should be involved in the lives of their children for the management of discipline at school, educators should acquaint themselves and learn to know learner’s home backgrounds in order to understand learners they are dealing with. In-service workshops about alternatives to corporal punishment for all educators in the two target rural secondary schools should be organised by the Department of Basic Education.
Thesis(M.Ed.(Community and Continuing Education)) -- University of Limpopo, 2019
Keywords: School governing bobdy; Secondary school; Discipline; School discipline; School management and organization -- South Africa -- Limpopo